Análise de metodologias e estratégias de testes de API rest: um estudo de caso - Fujiwara, Bruno Keichi (Universidade Federal de São Carlos, 2023)
The present work aims to present an analysis of API testing types, their characteristics, and the importance of these tests to ensure API quality. In addition, the concept of Behavior-Driven Development (BDD) and how it can be applied in API testing will be addressed. Some tools that can be used to implement BDD in API testing will also be presented, as well as a comparison between BDD techniques and automated API testing. The results indicate that API testing is essential to ensure API quality, as it allows verifying if the application meets the specified requirements and is functioning correctly. The use of BDD in performing these tests brings several benefits, such as greater clarity in communication between developers and clients, increased efficiency in bug detection, and ease of test maintenance. Furthermore, the comparison between BDD techniques and automated API testing demonstrated that both are important, complementary and can be used together to obtain better results.
Analysis of methodologies and testing strategies for REST API: a case study
Keywords: API; Testes de API; Behavior-Driven Development; BDD; Testes automatizados; CIENCIAS EXATAS E DA TERRA::CIENCIA DA COMPUTACAO::METODOLOGIA E TECNICAS DA COMPUTACAO::ENGENHARIA DE SOFTWARE